Bioinspired Perspiration‐Wicking Electronic Skins for Comfortable and Reliable Multimodal Health Monitoring - Xu, Yanting; Guo, Wei; Zhou, Shiqing; Yi, Haokun; Yang, Guoqing; Mei, Shuxing; Zhu, Kanhao; Wu, Hao; Li, Zhuo (Advanced functional materials, 2022)
Electronic skins (e‐skins) have gained tremendous attention in health monitoring and disease diagnosis. However, the accumulated sweat at the skin/e‐skin interface would compromise the comfort, reliability, and fidelity for long‐term monitoring. Here, inspired by the active liquid transport phenomenon in nature, a biomimetic gold/thermoplastic polyurethane/cellulose membrane (Au/TPU/CM) based e‐skin is reported that can “pump” perspiration from the interface immediately through the combination of gradient porosity and surface energy gradient. The resulting electrode possesses good conductivity (2.68 Ω sq–1), excellent flexibility (the resistance only fluctuated 1.1% and 0.4% after 10 000 bending cycles and 2500 tensile cycles, respectively), and outstanding water vapor transmission and water evaporation rate (2.2 and 7.1 times as much as that of cotton fabric, respectively). The ultrafast perspiration‐wicking capability not only improves the wearing comfort but also minimizes the measurement error of skin hydration and temperature due to perspiration, eliminates the risk of short circuit in sensor array, and reduces the noise level, significantly enhancing the accuracy and reliability of multimodal sensing in e‐skins. The design strategy may encourage more material and structure development in e‐skins with improved sweat tolerance. This study leverages controlled liquid transport principles in biosystems in e‐skin design and achieves active and unidirectional transportation of sweat away from the skin through the construction of dual porosity and surface energy gradients, preventing signal degradation and wearing discomfort caused by perspiration accumulation.